Effectiveness of the “Ular Tangga” Method Against the Motivation and Activeness of the Class of Pregnant Women in Ngepoh Village Dringu Sub District, Probolinggo Regency - Kasri Astuti; Rahmania Ambarika (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
One of the efforts to reduce maternal and child mortality is by implementing classes for pregnant women. However, the number of pregnant women participating in the class for pregnant women in Indonesia is still low. This is because pregnant women class participants feel bored with the method used. The purpose of the study was to determine the effectiveness of the application of the snake and ladder method on the motivation and activeness of attending classes for pregnant women in Ngepoh village, Dringu district, Probolinggo district. This type of research uses a quasi-experimental pre-post test design with a non-equivalent control group. This research was conducted for 3 months. The population in this study were all pregnant women in the second and third trimesters who had their pregnancy checked. The sample of this study amounted to 10 people. The results obtained indicate that based on the Wilcoxon test results indicate that value = 0.038 which means that there is an effect of the snake and ladder method on the motivation of pregnant women to take classes for pregnant women and at value = 0.046 which means that there is an effect of the snake and ladder method on the activity of pregnant women in participating in maternal classes. pregnant. It can be concluded that there is an increase in the motivation and activeness of mothers in attending classes for pregnant women.